Boost Full Bridge Bidirectional DC/DC Converter for Supervised Aeronautical Applications - Alberto Cavallo; Beniamino Guida; Luigi Rubino (International Journal of Aerospace Engineering)
The More Electrical Aircraft concept requires electronic devices able to efficiently and safely convert electrical power between different voltage levels. The entire realization of a bidirectional DC/DC converter, from design to validation phase, is here discussed in detail. First, a boost full bridge electrical structure is selected, adopting a Parallel Input Parallel Output (PIPO) interleaving technique and an optimal turns ratio selection for the transformers in order to reduce both weight and size of the equipment. Next, modulation schemes in both step-down and step-up modes are discussed. Successively ad hoc PI regulators for both operative modes are presented. A key idea of the paper is that the converter behavior must be related not only to the control strategy but also to a global supervision logic able to safely conduct the converter operations and to react from external stimuli. Thus, a finite state machine (FSM) approach is employed. An innovative strategy called buffer mode is presented, defined as an intelligent combination of buck and boost modes. Extensive simulations and experimental results are shown, in order to confirm the effectiveness of the proposed approach.